Challenges to publishing pharmacy resident research projects from the perspectives of residency program directors and residents (Pharmacy Practice, 2013)
Objective: To identify barriers to completing and publishing pharmacy residency research projects from the perspective of program directors and former residents.Methods: This was a cross-sectional survey of pharmacy residency program directors and former post-graduate year one and two residents. Directors of pharmacy residency programs whose residents present their projects at the Western States Conference (n=216) were invited to complete an online survey and asked to forward the survey to former residents of their program in 2009, 2010, or 2011. The survey focused on four broad areas: 1) demographic characteristics of the residency programs, directors, and residents; 2) perceived value of the research project; 3) perceived barriers with various stages of research; and 4) self-identified barriers to successful research project completion and publication.Results: A total of 32 program directors and 98 residents completed the survey. The minority of programs offered formal residency research training. Both groups reported value in the research project as part of residency training. Significantly more directors reported obtaining institutional review board approval and working through the publication process as barriers to the research project (46.7% vs. 22.6% and 73.3% vs. 43.0%, respectively p